ChemInform Abstract: A Solvent‐Free Approach to Glycosyl Amides: Toward the Synthesis of α‐N‐Galactosyl Ceramides. Issue 40 (October 2015) - Chennamadhavuni, Divya; Howell, Amy R.
Abstract Reduction of glycosyl azides to amines followed by coupling with p‐nitrophenol esters of lipids as key step provides α‐ and β‐glycosyl amides.